Hypoperfusion ratio predicts infarct growth during transfer for thrombectomy. Issue 4 (23rd September 2018) - Guenego, Adrien; Mlynash, Michael; Christensen, Soren; Kemp, Stephanie; Heit, Jeremy J.; Lansberg, Maarten G.; Albers, Gregory W.
Abstract : We hypothesized that automated assessment of collaterals on computed tomography perfusion can predict the rate of infarct growth during transfer from a primary to a comprehensive stroke center for endovascular stroke treatment. We identified consecutive patients (N = 28) and assessed their collaterals based on the hypoperfusion intensity ratio (HIR) prior to transfer. Infarct growth rate was strongly correlated with HIR ( r = 0.78, p < 0.001). Receiver operating characteristic analysis identified HIR ≥ 0.5 as optimal for predicting infarct growth. Patients with HIR ≥ 0.5 had a median infarct growth rate of 10.1ml/h (interquartile range [IQR] = 6.4–18.4) compared with 0.9ml/h (IQR = 0–2.8; p < 0.001) in patients with HIR < 0.5. Patients with HIR ≥ 0.5 had an 83% probability of significant core growth, whereas patients with HIR < 0.5 had an 88% probability of core stability. These preliminary data have the potential to guide decision making regarding whether repeat brain imaging should be performed after transfer to a comprehensive stroke center. Ann Neurol 2018;84:616–620